Pelatihan serta Pendampingan Penerapan Teknologi Aplikasi keluarga Cara’de bagi Kader Posyandu Anggrek di Desa Je’nemadinging Kabupaten Gowa - Esse Puji Pawenrusi; Sri Syatriani; Suarni Suarni; Kamariana Kamariana; Riamilah Riamilah; Eka Wahyuni; Muh. Dzulkifli MN (Jurnal Pengabdian Ilmu Kesehatan, 2025)
This community service program was held with the primary objective of improving the understanding and skills of Posyandu Anggrek cadres in conducting technology-based stunting surveys using the Cara'de application. Stunting is a chronic nutritional problem that impacts child growth and development and requires targeted intervention. Therefore, Posyandu cadres, as the frontline of health services, play a crucial role in collecting accurate nutritional data. The training was designed in eight face-to-face meetings and facilitated by five people, consisting of three lecturers and two students from the Makassar Health Sciences College, so that the knowledge transfer process was more structured. The series of activities included focus group discussions (FGDs) to explore initial understanding, technical training discussing the application's features, hands-on practice so that cadres could practice using Cara'de, and intensive mentoring to ensure all participants could optimally master the new skills. Evaluation results showed that the cadres not only understood the concept of stunting surveys but were also able to practice using the application independently to support valid, accurate, fast, and real-time child nutrition data collection. This success confirms a significant increase in cadre capacity, both in terms of knowledge and technical skills. Furthermore, this program is expected to improve the efficiency of Posyandu cadres, strengthen the health database, and support the development of more targeted nutrition policies and interventions. Thus, this activity significantly contributes to strengthening the local government's efforts to reduce stunting rates in Gowa Regency and serves as a model for strengthening technology-based public health services in rural areas.